Dentigerous cysts in primary dentition: Report of 2 cases - Delbem, Alberto Carlos Botazzo [UNESP]; Cunha, Robson Frederico [UNESP]; Afonso, Rebeca Lima [UNESP]; Bianco, Karina Gerhardt [UNESP]; Idem, Ana Paula [UNESP] (My University, 2006)
Dentigerous cysts are benign odontogenic cysts associated with the crowns of permanent teeth. They are usually single in occurrence and located in the mandible. The purpose of this case report was to describe the management of 2 dentigerous cysts in children. The treatments instituted were the extraction of the deciduous tooth involved followed by marsupialization in the first case and enucleation in the second one. Both treatments allowed rapid healing of the lesion and eruption of the permanent teeth without the need for orthodontic treatment.
Keywords: Deçiduous dentition; Dentigerous cyst; Odontogenic cysts; Oral surgery